Analysis of crocetane in crude oils and sediments: novel stationary phases for use in GC-MS - Barber, Cindy; Bastow, Trevor; Grice, Kliti; Alexander, Robert; Kagi, Robert (Pergamon-Elsevier, 2001)
Cyclodextrin GC stationary phases, well documented for their superior isomeric separation capabilities, have been investigated in the separation of crocetane (2,6,11,15-tetramethylhexadecane) and phytane (2,6,10,14-tetramethylhexadecane). Although crocetane has been attributed to methane oxidizing archaea, its general occurrence in crude oils and sediments is yet to be fully established due to difficulties associated with the GC?MS analysis since crocetane co-elutes with phytane when chromatographed on most liquid phase coated capillary columns. A method is described for the routine GC-MS analysis of crocetane and phytane in crude oils and sediments, using cyclodextrinstationary phases. Numerous derivatised cyclodextrin columns were investigated. A 50 m permethyl-b-cyclodextrin was found to give the best resolution (R=0.8 using hydrogen as the carrier gas and R=0.7 using helium).